The Role of Resilience in Quality of Life in a Productive-Age Population During the COVID-19 Pandemic - Nurcandra, Fajaria; Ronoatmodjo, Sudarto; Keliat, Budi Anna; Sudaryo, Mondastri Korib (UI Scholars Hub, 2023)
The COVID-19 pandemic has impacted various sectors and may trigger a decrease in quality of life (QoL), so resilience is urgently needed. This study aimed to analyze the role of resilience in the QoL of individuals during the second wave of the COVID-19 pandemic in East Jakarta, Indonesia. An explanatory sequential mixed methods study was conducted with a cross-sectional design. The QoL was measured using the Indonesian-HRQoL on 300 respondents through multistage cluster sampling. The explanatory qualitative approach involved Focus Group Discussions and in-depth interviews. A Cox regression was used to analyze the quantitative data. The proportion of poor QoL was 26.30%. Poor resilience (individual, family, and community) contributed to poor QoL during the pandemic. Realistic perceptions determined the role of individual resilience in QoL concerning gratitude, sincerity, patience, mutual reinforcement, accepting circumstances, implementing health protocols, cognitive emotion regulation, adaptability, and optimism. The age of family decision-makers, social support, and self-control determined the role of individual resilience in QoL. The role of community resilience in mental-emotional disorders and QoL was determined by the stability of the education system, health system, political/government system, and pandemic management system.